The educational systems of the United States and Germany--A comparison - Goodrich, Clara S. (My University, 1903)
Introduction: I. Means of furnishing education aside from schools—Unites States. The national government has a large share in the control and direction of educational thought and institutions. It has under its care, officially, the education of the Indians and Alaskans, and provides generously for rural and military education in two institutions expressly for the purpose, as well as in departments of colleges and universities for this kind of training. The government also provides millions for the impoverished South. The means, aside from schools, by which the government furnishes opportunity for the education of its people may be discussed under three heads: 1. The Bureau of Education. 2. The Smithsonian Institute. 3. Special Scientific Work.
The school systems of Germany, and the United States: a comparison
Citation: Goodrich, Clara S. The educational systems of the United States and Germany--A comparison. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Public Education; History of Education; United States; Germany; Theses; Manuscripts (documents)